STUDI KELAYAKAN PERANCANGAN PPEMBANGKIT LISTRIK TENAGA ANGIN DI PT. ALTRAK 1978 BALIKPAPAN - eka surya; Anwar f (Lembaga Penelitian Universitas Balikpapan, 2018)
Fossil fuels are depleting renewable energy needs. For that alternative energy is required i.e. wind energy. Wind energy can be designed into a wind power plant (PLT). PLT Wind planned office building of PT. Altrak 1978 is to supply 10% of the total load of the burden of office building of PT. Altrak 1978. This research begins with collecting and processing data on wind speed derived from Agency for meteorology, climatology and Geophysics (BMKG), NASA satellite and data processing of the anemometer so that it brings the potential of wind in the building Office PT Altrak 1978. With the potential of wind in the office building of PT. Altrak 1978 then selected a suitable wind turbines applied in the office building of PT. Altrak 1978 i.e. vertical wind turbines. To supply 10% load then determined a number of wind turbine FIRED POWER STATION components 854, batteries a number of 196, 854, 1 rectifier inverters with a capacity of 28kW. Based on the feasibility Based on the results of the economic analysis of the feasibility of the Discounted payback period (DPP) in the year to 21 obtained is negative (-), namely in the amount of Rp. 8,277,522,168.86 is not equal to the costs of his investment. Net Present Value (NPV) obtained-Rp. 17,367,942,738.86 (< 0) and the Profitability Index (PI) obtained-1.91.